Impact of public health intervention on knowledge, attitude and practice of workers and Escherichia coli prevalence in selected cattle abattoirs in Malaysia - Tukur, Adamu Muhammed (2016)
Background: The public health issues related to meat safety remains a major issue in the 21st century which affects both the advanced and third-world countries. Several outbreaks of diseases linked with food were associated Escherichia coli. Problem Statement: Inadequate provision of equipment and awareness on food safety are some of the factors that accelerate the dissemination of E.coli to the environment. An increase in the prevalence of pathogenic Escherichia coli among human population may hospitalization and even deaths. Justification: Incidence of food poisoning has been increasing over the last decade in Malaysia and E.coli was found to be the cause in many instances. Interventions including health education and awareness which focuses on food handlers can serve as a proactive measure in management and prevention of illnesses arising from ingestion of contaminated food items. Therefore, the main objective of this research focused on assessing the impact of an intervention in improving Knowledge, Attitude and Practice (KAP) abattoir workers and decreasing prevalence of E.coli in some selected abattoirs. Methodology: An intervention program in form occupational, food and environmental safety was conducted in the study. Impact of the intervention was assessed in two phases; pre and post intervention phases. Self-administered questionnaire and sample collections were used for assessment of KAP and prevalence of E.coli respectively. Findings: The mean scores for knowledge, Attitude and Practice, in the pre-intervention phase were 7.1±1.87, 4.3±0.73 and 5.5±1.01 respectively. While in the post-intervention phase the scores were 9.4±2.15, 4.7±0.48 and 5.8±0.93 respectively. Comparison of KAP score in pre and post intervention phases indicated significant difference in knowledge (p=0.000) and attitude (0.025) but no significant difference was observed in practice scores (p=0.115) based on the results. Significant reduction (p=0.04) in cfu/ml of waste water discharged all abattoirs into the environment was recorded. Carcass contamination was also found to be decreased in all abattoirs (p=0.033) after the intervention. The hands swab samples collected during the study showed that E.coli O157:H7 was isolated on hands of workers during work in two locations and the total prevalence during work was 9.4%. Non-O157:H7 was 34.5% in the preintervention phase. In the post intervention phase total prevalence during work was found to be 0% for E.coli O157:H7 and 27.8% for Non-O157:H7. Conclusion: Based on the findings the intervention program was found to have an impact towards improving workers KAP and reduction of E.coli prevalence in the Abattoir.